An Overview Of The Effect Of Online Gaming On The Grade Point Average (GPA) Of Faculty Of Medicine Students At YARSI University, Class Of 2023–2024, And Its Review From An Islamic Perspective - Devin Aurelia Sugiasti; Ferryal Basbeth; Aryenti Aryenti (International Journal of Health Engineering and Technology, 2026)
The development of online gaming potentially triggers addictive behaviors that could disrupt time management and decrease the Cumulative Grade Point Average (GPA) of medical students under a rigorous curriculum. In Islam, gaming is permissible (mubah) as long as it is beneficial and does not neglect academic or religious duties. This study aims to determine the influence of online gaming on the GPA of Medical Students at YARSI University Class of 2023–2024 and its review from an Islamic perspective.  This quantitative study with a survey design utilized a total sampling technique on active medical students of YARSI University Class of 2023–2024. A total of 272 respondents were obtained via an anonymous online questionnaire. Data were analyzed using the non-parametric Spearman Rank Correlation test. About 61.8% (168 students) of respondents were online gamers and 38.2% (104 students) were non-gamers. The average GPA was high (3.44 ± 0.29). The Spearman correlation test showed a correlation coefficient (r) = -0.053 with a significance value (p) = 0.496 (p>0.05). No significant difference was found in religious discipline between gamers and non-gamers. There is no statistically significant relationship between online gaming activities and the GPA of YARSI University medical students Class of 2023–2024 due to good self-regulation and time management. Based on the Islamic review, online gaming among respondents is categorized as mubah because it causes no harm or negligence (al-laghwu).